Engineering aspects of herbal and phytochemical processing: a Malaysian perspective - Abdul Aziz, Ramlan; Sarmidi, Mohd Roji; Kumaresan, Sivakumar; Chwan, Dominic Yee Foo (The Institution of Engineers, Malaysia, 2005)
Malaysia has a strong knowledge base of herbal product usage with a wide user base. Several Malaysian herbs have strong potential to be developed into global herbal medicines such as Tongkat Ali for impotence, Kacip Fatimah for hormone replacement therapy and Hempedu Bumi for diabetes and hypertension. In order to produce herbal medicines, standardisation, i.e. the process of producing herbal extracts or phytochemicals in which product potency is guaranteed through consistency in active compound profile and content level, is essential. Proper process development and effective analysis are the keys to standardisation. Process development of herbal processing in Malaysia involves modelling and optimisation studies of extraction equipment such as batch solid liquid extraction. In order to build effective process models and apply process design methods, physical and chemical data is required of the local herbs. At present very little knowledge is available of such parameters such as solubility, partition coefficient and heat transfer coefficients. In order to build a niche in the herbal medicine market, Malaysia can undertake product development based on local knowledge in terms of product formulation, form, and usage. Lastly, the experiences at the Chemical Engineering Pilot Plant (CEPP), the national research centre for process and product development in natural products and bioprocess is covered.